UWB Slotted Circular Disc Monopole Antenna with Inverted U Shaped Defected Ground Plane for Brain Cancer Detection - Vijayalakshmi, J.; Murugesan, G. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
In this paper the new design of UWB inscribed slotted circular disc monopole antenna is used in the detection of brain cancer is presented. The proposed antenna design consists of circular patch and the bandwidth is increased to cover the UWB frequency range of 3.2 GHZ to 10.6GHZ by embedding square shaped slot cut at the centre and a pair of inverted U shaped cut in the ground plane which gives a defected ground structure that provides the fractional bandwidth more than 110%[3.2 -10.6GHZ]. The proposed antenna is designed and fabricated for brain cancer detection. FR4 substrate is used with printed circular monopole radius of 15mm and with finite ground plane of (60mm x 50mm). It is designed with thick substrate with the thickness of h=1.6mm and high dielectric constant of εr=4.4. The voltage standing wave ratio is of (1-1.5). The proposed antenna design provides minimum return loss, better fractional bandwidth, satisfactorily radiation pattern.